Strategi Kepemimpinan dalam Meningkatkan Kinerja Karyawan pada PT. Multi Chandra Group di Bandar Lampung - Melan Susanty; Musolli (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2022)
This research is about Leadership Strategy in Improving Employee Performance at PT. Multi Chandra Group in Bandar Lampung. This study aims to determine how the leadership strategies applied by the leadership in improving employee performance at PT. Multi Chandra Group in Bandar Lampung. The research method used is a qualitative method. The results showed that the overall office employees of PT. Multi Chandra Group in Bandar Lampung has been able to carry out its work duties and responsibilities including service orientation, integrity, commitment, discipline, cooperation and leadership. leadership strategy in improving employee performance in the office of PT. Multi Chandra Group in Bandar Lampung in the form of, making disciplinary rules for all employees, providing clear job descriptions to employees related to their work, generating employee motivation at work, making daily reports as a form of performance appraisal, giving rewards to employees for their performance achievements and giving punishments. to employees who intentionally violate the rules set by PT. Multi Chandra Group in Bandar Lampung. Keywords: employee, performance, leadership strategy